Polymeric nanoparticles—Promising carriers for cancer therapy - Xiao, Xiao; Teng, Fei; Shi, Changkuo; Chen, Junyu; Wu, Shuqing; Wang, Bao; Meng, Xiang; Essiet Imeh, Aniekan; Li, Wenliang (Frontiers in Bioengineering and Biotechnology, 2022)
Polymeric nanoparticles (NPs) play an important role in controlled cancer drug delivery. Anticancer drugs can be conjugated or encapsulated by polymeric nanocarriers, which are known as polymeric nanomedicines. Polymeric nanomedicines have shown their potential in providing sustained release of drugs with reduced cytotoxicity and modified tumor retention, but until now, few delivery systems loading drugs have been able to meet clinical demands, so more efforts are needed. This research reviews the current state of the cancer drugs loading system by exhibiting a series of published articles that highlight the novelty and functions from a variety of different architectures including micelles, liposomes, dendrimers, polymersomes, hydrogels, metal-organic frameworks. These may contribute to the development of useful polymeric NPs to achieve different therapeutic purposes.